Analysis of the Influence of GDP, Exchange Rate, Gold Price, BI Rate, and IHSG on JII Islamic Investment Perspective - Nasution, Najlah Kholilah; Soemitra, Andri; Batubara, Maryam (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
Indonesia is a country with a Muslim-majority population. With a background of the majority of the Muslim population, the capital market issues various Sharia-based investments such as Sharia bonds, Sharia stocks, and Sharia mutual funds. The Islamic capital market has a role in driving the economy, including having an impact on real market growth through Sharia-based investments. The purpose of this study was to determine the direct and indirect effects of the GDP, Exchange Rate, Gold Price, BI Rate, and IHSG variables on the Jakarta Islamic Index from the perspective of Islamic investment in Indonesia for the 2016-2022 period. The method used in this study uses a quantitative approach with path analysis and uses the help of the Eviews 11 program. The results of this study indicate that GDP, Exchange Rate, and Gold Price have a significant negative effect on the Jakarta Islamic Index, but the BI Rate has no positive or significant effect on the Jakarta Islamic Index. IHSG has a positive and significant effect on the Jakarta Islamic Index. GDP has a positive and significant effect on the Composite Stock Price Index (IHSG). Meanwhile, Exchange Rates, Gold Prices, and the BI Rate have a negative and significant effect on the Composite Stock Price Index. IHSG is able to mediate GDP, Exchange Rate, Gold Price, and BI Rate against the Jakarta Islamic Index with a significant level of 5% and through a 95% confidence level.